2013
DOI: 10.1093/brain/awt249
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular heterotopia in 6q terminal deletion syndrome: role of the C6orf70 gene

Abstract: Periventricular nodular heterotopia is caused by defective neuronal migration that results in heterotopic neuronal nodules lining the lateral ventricles. Mutations in filamin A (FLNA) or ADP-ribosylation factor guanine nucleotide-exchange factor 2 (ARFGEF2) cause periventricular nodular heterotopia, but most patients with this malformation do not have a known aetiology. Using comparative genomic hybridization, we identified 12 patients with developmental brain abnormalities, variably combining periventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 45 publications
4
86
0
1
Order By: Relevance
“…Haploinsufficiency of ERMARD causes periventricular nodular heterotopia. 47 Because periventricular nodular heterotopia has been related to cardiovascular defects, it is conceivable that duplication of ERMARD plays a role in CHD. 48 By combining genes present in de novo CNVs, in overlapping CNVs (between our patients or public databases), and from TFBS analyses (http://hgdownload.soe.ucsc.edu/ goldenPath/hg19/database/tfbsConsSites.txt.gz), we identified a set of 113 candidate genes for CHD (Table VI in the Data Supplement) and a short list of 10 top-candidate genes (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Haploinsufficiency of ERMARD causes periventricular nodular heterotopia. 47 Because periventricular nodular heterotopia has been related to cardiovascular defects, it is conceivable that duplication of ERMARD plays a role in CHD. 48 By combining genes present in de novo CNVs, in overlapping CNVs (between our patients or public databases), and from TFBS analyses (http://hgdownload.soe.ucsc.edu/ goldenPath/hg19/database/tfbsConsSites.txt.gz), we identified a set of 113 candidate genes for CHD (Table VI in the Data Supplement) and a short list of 10 top-candidate genes (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a role of the heterotrimeric G-protein (Gαi2) was recently suggested in cortical development, and the encoding gene (GNAI2) was found mutated in a single PVH patient [196]. Another candidate gene playing a role in this cortical malformation is C6orf70 (ERMARD, for ER-membrane associated RNA degradation), found mutated in a patient with PVH [197].…”
Section: A Periventricular Nodular Heterotopias (Pvh) and Ventricularmentioning
confidence: 99%
“…Defects in progenitor cells, neuronal positioning and terminal translocation were identified by in utero electroporation. Furthermore, down-regulation of the α subunit, Gαi2, or C6orf70, affects neuron morphology and induces migration defects during corticogenesis in rodents [196,197].…”
Section: 23b Animal Models and Functional Studiesmentioning
confidence: 99%
“…The subunits of the npBAF complex are essential for neural-progenitor proliferation, and mice with reduced dosage for the genes encoding these subunits have defects in neuraltube closure similar to those in human spina bifida. 29 A more recent study by Conti et al 30 showed that a 1.2 Mb SRO common to 12 patients in the 6q27 region contains plausible genes THBS2, PHF10, TCTE3, DLL1, WDR27, and C6orf70. Of the 12 patients reported in the study, 9 patients had PNH, in addition to other brain malformations.…”
Section: Facial Dysmorphismmentioning
confidence: 99%